Complex regional pain syndrome: An international survey of clinical practice. (22nd August 2019) - Grieve, Sharon; Llewellyn, Alison; Jones, Louise; Manns, Sarah; Glanville, Victoria; McCabe, Candida S.
Abstract: Background: Published guidelines promote best practice in complex regional pain syndrome (CRPS) treatment and management; however, these recommendations are not always applied in clinical practice. Understanding existing care internationally will help inform future patient and health professional service delivery, education initiatives and content of clinical guidelines. Methods: An e‐survey was conducted in order to gain an insight into routine CRPS clinical practice. Health professionals and academics, from the field of CRPS, were recruited from an international population. Quantitative and qualitative data were elicited. Data were mapped onto a framework to identify macro‐regional factors. Results: Of the 260 survey respondents, 96% ( n  = 241) provided clinical care for people with CRPS, with academics not involved in patient care also responding. Half of respondents expressed difficulty in recognizing the symptoms of CRPS but treatment aims corresponded with published guidelines. However, a lack of resources and fragmented care were reported as barriers to early intervention. Service constraints were most frequently reported by European respondents. Five themes emerged from the qualitative data: the benefit of interdisciplinary working; the importance of symptom management; need for early diagnosis and intervention; establishing a collaborative partnership with patients; the value of education for patients and health professionals. Conclusions: Our data suggest that more work is required to raise awareness of the Budapest CRPS diagnostic criteria so as to promote early diagnosis and intervention. Future work to optimize clinical effectiveness should consider enhancing interdisciplinary service delivery that encourages a collaborative patient/clinician partnership; includes excellent patient education; and addresses modifiable patient‐related factors. Significance: Health professionals expressed some level of difficulty recognizing the signs and symptoms of CRPS despite the majority of health professionals having had clinical experience exceeding 6 years in the field of CRPS. More work is required to raise awareness amongst clinicians of the Budapest CRPS diagnostic criteria so as to promote early diagnosis and intervention Health professionals' treatment aims reflected the current clinical guidelines however, a lack of resources and fragmented care were frequently cited as barriers to achieving these.